2001
DOI: 10.1097/00003643-200111000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium as part of balanced general anaesthesia with propofol, remifentanil and mivacurium: a double-blind, randomized prospective study in 50 patients

Abstract: Background and objective To test the hypothesis that magnesium sulphate reduces the amount of remifentanil needed for general anaesthesia in combination with propofol and mivacurium, we studied 50 patients undergoing elective pars plana vitrectomy in a double-blind, randomized prospective fashion. Methods Magnesium sulphate (50 mg kg ±1 body weight) or placebo (equal volume of NaCl) was given slowly intravenously after induction of anaesthesia with propofol 1±2 mg kg ±1 . Anaesthesia was maintained with propof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 22 publications
(22 reference statements)
4
31
0
1
Order By: Relevance
“…In our study as in previous reports, the fentanyl requirements were titrated according to haemodynamic changes. Other work using doses of magnesium similar to ours have been shown to produce reductions in analgesic requirements both during and after surgical interventions [13].…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…In our study as in previous reports, the fentanyl requirements were titrated according to haemodynamic changes. Other work using doses of magnesium similar to ours have been shown to produce reductions in analgesic requirements both during and after surgical interventions [13].…”
Section: Discussionmentioning
confidence: 70%
“…[12] concluded that intravenous administration of magnesium sulphate reduced propofol infusion requirements, whereas Schulz‐Stubner et al . [13] observed that propofol consumption remained unchanged after using magnesium sulphate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations